Epigenetic modification and uniparental inheritance of H19 in Beckwith-Wiedemann syndrome. Issue 5 (May 1997) - Catchpoole, D; Lam, W W; Valler, D; Temple, I K; Joyce, J A; Reik, W; Schofield, P N; Maher, E R
Abstract : Beckwith-Wiedemann syndrome (BWS) is a congenital overgrowth syndrome associated with a characteristic pattern of visceromegaly and predisposition to childhood tumours. BWS is a genetically heterogeneous disorder; most cases are sporadic but approximately 15% are familial and a small number of BWS patients have cytogenetic abnormalities involving chromosome 11p15. Genomic imprinting effects have been implicated in familial and non-familial BWS. We have investigated the molecular pathology of 106 sporadic BWS cases; 17% (14/83) of informative cases had uniparental disomy (UPD) for chromosome 11p15.5. In each case UPD appeared to result from a postzygotic event resulting in mosaicism for segmental paternal isodisomy. The critical region for isodisomy was refined to a 25 cM interval between D11S861 and D11S2071 which contained the IGF2, H19, and p57(KIP2) genes. In three cases isodisomy for 11q markers was detected but this did not extend further than 11q13-q21 suggesting that complete chromosome 11 disomy may not produce a BWS phenotype. The allele specific methylation status of the H19 gene was investigated in 80 sporadic BWS cases. All 13 cases with UPD tested displayed hypermethylation consistent with an excess of paternal H19 alleles. In addition, five of 63 (8%) cases with normal biparental inheritance had H19 hypermethylation consistent with an "imprinting centre" mutation (ICM) or "imprinting error" (IE) lesion. The phenotype of patients with putative ICM/IE mutations was variable and overlapped with that of non-UPD sporadic BWS cases with normal H19 methylation. However, exomphalos was significantly (p < 0.05) more common in the latter group. These findings may indicate differential effects on the expression of imprinted genes in chromosome 11p15 according to the precise molecular pathology. Analysis of H19 methylation is useful for the diagnosis of both UPD or altered imprinting in BWS and shows that a variety of molecular mechanisms may cause relaxation of IGF2 imprinting in BWS.